Method for immobilizing photocatalyst on foamed ceramic
By solidly loading the nanophotocatalysts onto the pore surface of foam ceramics, the problem of difficulty in recycling and easy to cause secondary pollution is solved, efficient and stable photocatalytic reactions are achieved, and the feasibility of its industrial application is promoted.
Patent Information
- Application Number
- CN202411758541.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-04-22
AI Technical Summary
Nano-photocatalysts are difficult to recover during use, which easily causes secondary pollution, hindering their widespread use in industrial applications.
By mixing the nanophotocatalyst with an organic binder, a dispersant, a thickener and an organic solvent, a viscous photocatalyst slurry is formed. The foam ceramic is then immersed in the slurry, and the nanophotocatalyst is solidly loaded to the pore surface of the foam ceramic after drying and low temperature calcination.
The stable solid loading of the photocatalyst is achieved, the dispersion and difficulty in recycling of nanophotocatalysts are avoided, the efficiency and stability of the photocatalytic reaction are improved, and the product can be recycled multiple times, which is low-carbon and green.
Smart Images

Figure CN119857472A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of photocatalyst use and relates to a method for immobilizing photocatalyst on foam ceramics. Background Art
[0002] As people's awareness of environmental protection continues to increase, water pollution issues are becoming more and more important, especially organic pollution, which often causes a decrease in dissolved oxygen in water, leading to the death of aquatic organisms; under anaerobic conditions, microbial decomposition will produce difficult gases such as hydrogen sulfide and sulfide alcohols, causing water quality to deteriorate; some organic matter itself is toxic, causing poisoning of aquatic organisms and threatening their survival. In addition, organic wastewater entering the human body will also threaten human health, such as carcinogenicity, teratogenicity, endocrine disruption and other health problems. Therefore, how to control and eliminate the hazards caused by organic pollutants has become an important issue.
[0003] Photocatalytic technology is an efficient, simple, green and sustainable catalytic oxidation technology. It has a good catalytic effect on air pollutants and water pollutants, such as aromatic hydrocarbons, petroleum-based compounds, petroleum hydrocarbons, chlorinated hydrocarbons, pesticides, volatile organic compounds (VOC), dyes and other organic materials. When the energy of the photon is greater than the bandgap width (hv ≥ Eg), the electrons of the photocatalyst are excited to jump from the valence band to the conduction band, and holes (h + ), the conduction band forms photogenerated electrons (e - ), hole (h + ) and photogenerated electrons (e - ) reacts with water to generate superoxide radicals (·O 2- ), hydroxyl radical (·OH), superoxide radical (·O 2- ), hydroxyl radicals (·OH) react with organic matter in water to produce CO 2 When photons continuously irradiate the photocatalyst, there will be continuous holes (h + ) and photogenerated electrons (e - ) is generated, and then the organic matter reacts to produce CO 2 Therefore, the use of photocatalyst technology to treat organic pollutants in water can truly achieve green, efficient and sustainable development.
[0004] In order to increase the reaction rate of photocatalysts, researchers have found that increasing the contact area between photocatalysts and light is a more effective way. They have found that the finer the photocatalyst particles, the larger the specific surface area, the more sufficient the contact with light, and the faster the reaction rate. Therefore, in order to increase the reaction rate, photocatalysts generally use nano-sized particles. However, although nanoparticles have good effects, they are easy to disperse in water, difficult to recycle, and easy to cause secondary pollution, which hinders the industrial application of photocatalysts. Summary of the invention
[0005] Purpose of the Invention
[0006] The purpose of the present invention is to provide a method for immobilizing photocatalysts on foam ceramics that is easy to recycle and not prone to secondary pollution, in order to solve the problem that nano photocatalysts are difficult to recycle and are prone to secondary pollution during use.
[0007] Technical Solution
[0008] A method for immobilizing a photocatalyst on a foam ceramic comprises the following steps:
[0009] Step 1: Mix the nano-photocatalyst with an organic binder, a dispersant, a thickener and an organic solvent in proportion and mix them evenly to obtain a viscous photocatalyst slurry;
[0010] Step 2: Clean the foam ceramic to ensure that there are no impurities inside the foam ceramic, and cut it into any required size;
[0011] Step 3: Immerse the cleaned foam ceramics in the viscous photocatalyst slurry, take them out and dry them;
[0012] Step 4: After the foam ceramic loaded with the photocatalyst slurry is completely dried, it is calcined at a low temperature, and the nano-photocatalyst can be fixed on the pore surface of the foam ceramic.
[0013] Furthermore, in step one, the organic binder includes: acrylates, alkyd resins, polyurethanes or epoxy resins; the dispersant includes: fatty acids, aliphatic amides, esters or low molecular waxes; the thickener includes: polysaccharide or polypeptide thickener; the organic solvent includes: alcohols, ketones, aromatic hydrocarbons, aliphatic hydrocarbons, aliphatic hydrocarbons, halogenated hydrocarbons, ethers or lipids.
[0014] Furthermore, in step one, the photocatalyst is an inorganic semiconductor material photocatalyst; the ratio of nano-photocatalyst particles to organic binder, dispersant, thickener and organic solvent refers to that the nano-photocatalyst content is greater than or equal to 1%wt of the total mass, the organic binder is 1% to 30%wt of the total mass, the dispersant is 0.1 to 10%wt of the total mass, the thickener is 0.1% to 10%wt of the total mass, and the rest are organic solvents, and the organic solvent is greater than or equal to one type of solvent used alone or in combination.
[0015] Furthermore, in the step 1, the mixing method includes ball milling and stirring; the amount of balls added to the ball mill is not less than 20% of the volume of the ball mill, the diameter of the grinding balls is 5 mm to 20 mm, the ball milling speed is not less than 100 rpm, and the ball milling time is not less than 5 min; the stirring is magnetic stirring or mechanical stirring, the stirring speed is not less than 100 rpm, and the mixing time is not less than 10 min.
[0016] Furthermore, in step 2, the foam ceramic refers to foam ceramic with an average pore size of 40 ppi or more; and the cleaning is carried out by ultrasonic cleaning or water flushing.
[0017] Furthermore, in the step three, the immersion refers to completely immersing the foam ceramic in the slurry, the immersion time is not less than 2 seconds, and the number of immersions is not less than 1 time; and the drying refers to natural drying in a cool and ventilated place.
[0018] Furthermore, in the step 4, complete drying means that there is no sticky slurry on the surface of the foam ceramic; the temperature of low-temperature calcination is 200°C-700°C; the insulation time is more than 10 minutes, and after cooling, the nano-photocatalyst can be fixed on the pore surface of the foam ceramic; the heating rate is 1-20°C / min, and the low-temperature calcination uses an atmosphere furnace, a vacuum furnace or a non-atmosphere furnace.
[0019] Furthermore, in the step 4, a double-layer atmosphere furnace is used for low-temperature calcination, including an outer shell, an inner side of the outer shell is provided with an insulation inner seat, a heating resistance wire is provided on the inner side of the control outer shell and at the lower end of the insulation inner seat, an outer furnace body is fixed on the inner side of the insulation inner seat, a first feeding cavity is provided inside the outer furnace body, an outer furnace door is provided on the outer side of the outer shell and outside the first feeding cavity, the outer furnace door is fitted with the insulation inner seat, an inner furnace body is fixed on the inner side of the outer furnace body, and a second feeding cavity is provided inside the inner furnace body. cavity, the inner side of the outer furnace body and the lower end located between the first feeding cavity and the second feeding cavity is rotatably connected with a support shaft, the outer side of the support shaft is fixed with an inner furnace door, the inner furnace door is fitted with the inner furnace body, a cooling pipe is fixed on the inner side of the upper end of the outer shell, the lower ends of the cooling pipe are respectively located on the thermal insulation inner seat, the outer furnace body, and the inside of the inner furnace body and are fixed to the thermal insulation inner seat, the outer furnace body and the inner furnace body; an air inlet pipe and an air outlet pipe are respectively fixed on the top of the outer shell, and the lower ends of the air inlet pipe and the air outlet pipe both penetrate the outer furnace body and extend to the inner side of the outer furnace body.
[0020] Furthermore, an electromagnetic valve is arranged between the outer side of the thermal insulation inner seat and the outer furnace door; a reduction motor is fixed on the inner side of the outer shell, a coupling is fixed on the output end of the reduction motor, the coupling is a thermal insulation material, and the end of the coupling away from the reduction motor passes through the outer furnace body and is fixed to the support shaft; an insulation jacket is fixed on the outer side of the inner part of the outer furnace body and located between the coupling and the support shaft, the outer sides of the coupling and the support shaft are both in contact with the inner side of the insulation jacket, and the coupling, the insulation jacket and the support shaft are coaxially arranged.
[0021] Furthermore, a plurality of heat conducting plates are evenly fixed to the top of the inner side of the inner furnace body, and the upper ends of the plurality of heat conducting plates are all in contact with the cooling pipe. The cooling pipe is located outside the outer shell, and the outer periphery is coated with heat insulation material.
[0022] Advantages and effects
[0023] The present invention utilizes the porosity and stability of foam ceramics to solidify the photocatalyst on the surface of the foam ceramic pores, allowing light to easily penetrate and react with the solidified photocatalyst. The organic binder is solidified and carbonized through low-temperature calcination technology to form a carbon with a flocculent porous structure. While the flocculent porous carbon solidifies the photocatalyst, it also performs non-metallic carbon doping modification on the photocatalyst to enhance the photocatalytic response of the photocatalyst. The present invention is simple to operate, and the product maintains a high catalytic efficiency under both ultraviolet light and natural light. The product can be recycled multiple times while maintaining stable performance. The reaction process can be completely static, without the need for additional energy, making the reaction more low-carbon and green. The present invention facilitates the industrial transformation of photocatalysts.
[0024] The double-layer atmosphere furnace is designed with overall structural coordination, so that when the inner side of the outer furnace body is heated and the inner furnace door is closed, the heat is effectively isolated from the outer side of the inner furnace body. When the temperature inside the outer furnace body reaches the temperature required for low-temperature calcination: 200℃-700℃, the inner furnace door is opened through the reduction motor control, so that the temperature inside the inner furnace body is instantly heated up, and the foam ceramic after solidification is rapidly heated up, so that the binder is carbonized more fully; the inner furnace door can also be kept open to heat up and cool down the inner and outer furnace bodies together, so as to achieve conventional heating and cooling. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The present invention is further described below in conjunction with the accompanying drawings and specific implementation methods. The protection scope of the present invention is not limited to the following description.
[0026] Figure 1 This is the process flow chart of the patented method;
[0027] Figure 2 This is a scanning electron microscope image of the foam ceramic after the photocatalyst is immobilized in Example 1;
[0028] Figure 3 This is an X-ray photoelectron spectrum image of the foam ceramic surface after the photocatalyst is immobilized in Example 1;
[0029] Figure 4 This is a schematic diagram of the degradation of methylene blue solutions with different concentrations after the photocatalyst is immobilized in Example 1;
[0030] Figure 5 This is a schematic diagram of the cyclic regeneration performance of the photocatalyst after immobilization in Example 1;
[0031] Figure 6 It is the overall structural schematic diagram of the double-layer atmosphere furnace;
[0032] Figure 7 This is a schematic diagram of the structure when the outer furnace door of the double-layer atmosphere furnace is opened;
[0033] Figure 8It is a schematic diagram of the structure of the inner side of the outer furnace of the double-layer atmosphere furnace;
[0034] Fig. 9 It is a schematic diagram of the structure of the inner side of the furnace body in a double-layer atmosphere furnace.
[0035] Explanation of the reference numerals: 1. outer shell; 2. thermal insulation inner seat; 3. outer furnace door; 4. solenoid valve; 5. outer furnace body; 6. inner furnace body; 7. first feeding cavity; 8. air inlet pipe; 9. air outlet pipe; 10. cooling pipe; 11. reduction motor; 12. coupling; 13. thermal insulation jacket; 14. support shaft; 15. inner furnace door; 16. second feeding cavity; 17. heat conducting sheet. DETAILED DESCRIPTION
[0036] like Figure 1 As shown, a method for immobilizing photocatalyst on foam ceramics comprises the following steps:
[0037] Step 1: Mix the nano-photocatalyst with an organic binder, a dispersant, a thickener and an organic solvent in proportion and mix them evenly to obtain a viscous photocatalyst slurry;
[0038] Step 2: Clean the foam ceramic to ensure that there are no impurities inside the foam ceramic, and cut it into any required size;
[0039] Step 3: Immerse the cleaned foam ceramics in the viscous photocatalyst slurry, take them out and dry them;
[0040] Step 4: After the foam ceramic loaded with the photocatalyst slurry is completely dried, it is calcined at a low temperature, and the nano-photocatalyst can be fixed on the pore surface of the foam ceramic.
[0041] In step one, the organic binder includes: acrylates, alkyd resins, polyurethanes or epoxy resins; the dispersant includes: fatty acids, aliphatic amides, esters or low molecular waxes; the thickener includes: polysaccharide or polypeptide thickener; the organic solvent includes: alcohols, ketones, aromatic hydrocarbons, aliphatic hydrocarbons, aliphatic hydrocarbons, halogenated hydrocarbons, ethers or lipids.
[0042] In step one, the nano-photocatalyst is a conventional nano-size commercially available, and the photocatalyst is an inorganic semiconductor material photocatalyst; the ratio of nano-photocatalyst particles to organic binder, dispersant, thickener and organic solvent refers to that the nano-photocatalyst content is greater than or equal to 1%wt of the total mass, the organic binder is 1% to 30%wt of the total mass, the dispersant is 0.1 to 10%wt of the total mass, the thickener is 0.1% to 10%wt of the total mass, and the rest are organic solvents, and the organic solvent is greater than or equal to one type of solvent used alone or in combination.
[0043] In step 1, the mixing method includes ball milling and stirring; the amount of balls added to the ball mill is not less than 20% of the volume of the ball mill, the diameter of the grinding balls is 5 mm to 20 mm, the ball milling speed is not less than 100 rpm, and the ball milling time is not less than 5 min; the stirring is magnetic stirring or mechanical stirring, the stirring speed is not less than 100 rpm, and the mixing time is not less than 10 min.
[0044] In step 2, the foam ceramic refers to foam ceramics with an average pore size of 40 ppi or more; and the cleaning is carried out by ultrasonic cleaning or water washing.
[0045] In step three, the immersion refers to completely immersing the foam ceramic in the slurry, the immersion time is not less than 2 seconds, and the number of immersions is not less than 1 time; and the drying refers to natural drying in a cool and ventilated place.
[0046] In step 4, complete drying means that there is no sticky slurry on the surface of the foam ceramic; the temperature of low-temperature calcination is 200℃-700℃; the temperature is kept for more than 10 minutes, and after cooling, the nano-photocatalyst can be fixed on the surface of the foam ceramic pores. The heating rate is 1-20℃ / min, and the low-temperature calcination can be performed in an atmosphere furnace, a vacuum furnace, or a non-atmosphere furnace.
[0047] In step 4, this embodiment uses and provides a low-temperature calcination double-layer atmosphere furnace, such as Figure 6 to Figure 9As shown, it includes an outer shell 1, an inner side of the outer shell 1 is provided with an insulation inner seat 2, a heating resistance wire is provided on the inner side of the control outer shell 1 and at the lower end of the insulation inner seat 2, an outer furnace body 5 is fixed on the inner side of the insulation inner seat 2, a first feeding cavity 7 is provided inside the outer furnace body 5, an outer furnace door 3 is provided on the outer side of the outer shell 1 and outside the first feeding cavity 7, the outer furnace door 3 is fitted with the insulation inner seat 2, an inner furnace body 6 is fixed on the inner side of the outer furnace body 5, a second feeding cavity 16 is provided inside the inner furnace body 6, and the inner side of the outer furnace body 5 and the first feeding cavity 7 and The lower end between the second feeding cavity 16 is rotatably connected with a support shaft 14, and an inner furnace door 15 is fixed to the outer side of the support shaft 14, and the inner furnace door 15 is in contact with the inner furnace body 6. A cooling pipe 10 is fixed to the inner side of the upper end of the outer shell 1, and the lower ends of the cooling pipe 10 are respectively located inside the thermal insulation inner seat 2, the outer furnace body 5, and the inner furnace body 6 and are fixed to the thermal insulation inner seat 2, the outer furnace body 5 and the inner furnace body 6; an air inlet pipe 8 and an air outlet pipe 9 are respectively fixed to the top of the outer shell 1, and the lower ends of the air inlet pipe 8 and the air outlet pipe 9 both penetrate the outer furnace body 5 and extend to the inner side of the outer furnace body 5. A solenoid valve 4 is arranged between the outer side of the heat-insulating inner seat 2 and the outer furnace door 3; a reduction motor 11 is fixed on the inner side of the outer shell 1, and a coupling 12 is fixed on the output end of the reduction motor 11. The coupling 12 is made of heat-insulating material, and the end of the coupling 12 away from the reduction motor 11 passes through the outer furnace body 5 and is fixed to the support shaft 14; a heat-insulating jacket 13 is fixed on the outer side of the inner side of the outer furnace body 5 and located between the coupling 12 and the support shaft 14. The outer sides of the coupling 12 and the support shaft 14 are both fitted with the inner side of the heat-insulating jacket 13, and the coupling 12, the heat-insulating jacket 13 and the support shaft 14 are coaxially arranged. The arrangement of the coupling and the heat-insulating jacket can effectively reduce the heat in the furnace body from being conducted to the reduction motor, protect the reduction motor, and pass the coolant / cooling gas into the cooling pipe in combination with the heat-conducting sheet to achieve rapid cooling of the inner furnace body. A plurality of heat conducting sheets 17 are evenly fixed to the top of the inner side of the inner furnace body 6, and the upper ends of the plurality of heat conducting sheets 17 are all in contact with the cooling pipe 10. The cooling pipe 10 is located outside the outer shell 1, and the outer periphery is covered with a heat preservation material. The outer shell 1 is provided with switches for controlling the electromagnetic valve 4, the reduction motor 11 and the heating resistance wire.
[0048] The use process of the low-temperature calcining double-layer atmosphere furnace is as follows: when the inner furnace door 15 is always open, the low-temperature calcining double-layer atmosphere furnace can be used as a conventional atmosphere furnace; when the foam ceramic needs to be rapidly heated, the outer furnace door 3 is first opened, and the reduction motor 11 is started to drive the coupling 12 and the support shaft 14 to rotate, and the inner furnace door 15 is driven to flip open, and the foam ceramic is placed inside the inner furnace body 6, and then the outer furnace door 3 is closed. At this time, nitrogen is filled into the outer furnace body 5 and the inner furnace body 6 through the air inlet and outlet operations of the air inlet pipe 8 and the air outlet pipe 9, and then the inner furnace door 15 is controlled to be closed. At this time, the outer furnace body 5 is controlled to heat up. When the temperature inside the outer furnace body 5 reaches 200°C to 700°C, the inner furnace door 15 is controlled to open so that heat flows into the inner side of the inner furnace body 6 to instantly heat up, thereby realizing the rapid heating and calcining operation of the solid-loaded foam ceramic;
[0049] After calcination, heating is stopped and coolant is introduced into the cooling pipe 10 to quickly cool down the inner side of the outer furnace body 5 and the inner furnace body 6. The cooling efficiency of the cooling pipe 10 on the inner side of the inner furnace body 6 is improved in conjunction with the heat conducting sheet 17. When the temperature of the inner side of the outer furnace body 5 and the inner furnace body 6 drops to room temperature, the product is taken out from the turntable with the outer furnace door 3 and the inner furnace door 15 both opened.
[0050] Example 1
[0051] Weigh 2g of nano-TiO 2 (Degussa P-25) powder, 2g polyvinyl butyral, 0.2g triethanolamine, 0.8g butyl benzyl phthalate, 10g ethanol and 5g butanone were poured into the ball mill and milled at a speed of 400r / min for 24h. The ball mill adopts positive and reverse alternating ball milling, and it stops for 5min every 10min of operation to ensure that the ball mill has enough time to dissipate heat and prevent the temperature from rising and causing the slurry to deteriorate. After ball milling, a viscous TiO 2 Slurry.
[0052] Immerse all the cleaned and dried foam ceramic blocks in the slurry, keep for 30 seconds, slowly extract them, and place them in a cool place to dry. After the slurry on the surface of the foam ceramic solidifies, perform the second immersion. The immersion method is the same as the first immersion method. The foam ceramics after immersion are placed in a cool place to dry. After they are completely dried, they are calcined at a low temperature in a double-layer atmosphere furnace. The sample is placed in the inner furnace body of the double-layer atmosphere furnace and nitrogen is introduced for protection. When the outer furnace body reaches the set temperature of 400°C, the inner furnace door is opened and the heating is maintained at 400°C for calcination. After calcination for 2 hours, coolant is introduced into the cooling pipe for cooling. TiO 2 The nanoparticles are immobilized on the pore surface of the foam ceramic.
[0053] The immobilized foam ceramics were characterized, such as Figure 2 As shown, the scanning electron microscope image of the foam ceramic after the photocatalyst is immobilized. Figure 2 a is 10 3 times, Figure 2 b is 2×10 3 times, Figure 2 c is 10 4 times, Figure 2 d is 2×10 5 times. Figure 2 It can be seen that the photocatalyst is evenly covered on the surface of the foam ceramic and forms a flocculent porous structure. The coating after the photocatalyst is immobilized was analyzed by X-ray photoelectron spectroscopy. Figure 3 As shown, Figure 3 a is O1s, Figure 3 b is C1s, Figure 3 c is Ti2p, Figure 3d is the score. Figure 3 It can be seen that the coating after solidification has a C=C structure, indicating that the binder is carbonized. After the binder is carbonized, it not only has a curing effect on the photocatalyst, but also has a doping and modification effect on the photocatalyst.
[0054] Performance test, the immobilized TiO 2 The foam ceramic particles were placed in 150 ml of 50 mg / L, 100 mg / L, 150 mg / L, and 200 mg / L methylene blue solutions for photocatalytic performance testing. Figure 4 As shown in a, the degradation rate of 50mg / L methylene blue solution reached 94% after 450min, the degradation rate of 100mg / L methylene blue solution reached 91% after 660min, and the degradation rates of 150mg / L and 200mg / L methylene blue solutions reached more than 90% at 840min and 960min respectively. The test was still in a completely static state under natural light. The test location was 40°39′N, 121°25′E in May. After two days of daylight exposure, Figure 4 As shown in Fig. b, the degradation rates of 50 mg / L, 100 mg / L, 150 mg / L, and 200 mg / L methylene blue solutions were 95.08%, 92.24%, 82.43%, and 70.00%, respectively. The regeneration cycle performance was tested under ultraviolet light for 8 h. Figure 5 As shown in a, after 10 regeneration cycles, the degradation rate of 50 mg / L remained above 91.59%, the degradation rate of 100 mg / L remained above 90%, and the degradation rates of 150 mg / L and 200 mg / L remained at 70.12% and 60.11%, respectively. The natural light regeneration cycle test was carried out in a completely static state from 8:00 am to 18:00 pm. Figure 5 As shown in Figure b, the degradation rate of 50 mg / L is maintained at more than 80.62%, the degradation rate of 100 mg / L is maintained at more than 78.94%, and the degradation rates of 150 mg / L and 200 mg / L are maintained at 39.09% and 35.29% respectively. This shows that the invention has the performance of recycling, and can be completely static during use, making the reaction more energy-saving and green, and solving the problem of nano-photocatalysts being difficult to recycle and prone to secondary pollution.
[0055] Example 2
[0056] Weigh 5g of nano ZnO powder, 3g of methyl acrylate, 0.7g of stearic acid, 1g of stearyl alcohol, 20g of ethanol and 5g of acetone into a ball mill and mill for 20h at a speed of 300r / min. The ball mill adopts positive and reverse alternating ball milling, and pauses for 5min every 10min of operation to ensure that the ball mill has enough time to dissipate heat and prevent the slurry from deteriorating due to temperature rise. After ball milling, a viscous ZnO slurry can be obtained.
[0057] Immerse all the cleaned and dried foam ceramic blocks in the slurry, keep for 40 seconds, slowly extract them, and place them in a cool place to dry. After the slurry on the surface of the foam ceramic solidifies, perform a second immersion. The immersion method is the same as the first immersion method. The impregnated foam ceramics are placed in a cool place to dry. After they are completely dry, they are calcined at low temperature in a muffle furnace at a calcination temperature of 350°C for 2 hours. After cooling, the ZnO particles are fixed to the surface of the foam ceramic pores.
[0058] Performance testing, the foam ceramics loaded with ZnO nanoparticles were placed in 150ml, 50mg / L methylene blue solution, and the photocatalytic performance was tested under ultraviolet light and repeated multiple cycles. The results showed that after 450min, the degradation rate reached more than 86.24%, and after 10 regeneration cycles, the degradation rate could still reach more than 84.46%.
[0059] Example 3
[0060] Weigh 1g of nano B 2 O 3 Powder, 2g toluene diisocyanate, 0.3g ethylene acrylic acid, 1g stearyl alcohol, 20g methanol and 5g tetrahydrofuran were poured into a beaker and stirred at 600r / min for 24h using a magnetic stirrer to form a viscous slurry B. 2 O 3 Slurry.
[0061] Immerse all the cleaned and dried foam ceramic blocks in the slurry and keep them for 30 seconds. After slowly extracting them, place them in a cool place to dry. After the slurry on the surface of the foam ceramic solidifies, perform the second immersion. The immersion method is the same as the first immersion method. The foam ceramics after immersion are placed in a cool place to dry. After they are completely dry, they are calcined at low temperature in a muffle furnace. The calcination temperature is 230℃ and the temperature is kept for 4 hours. After cooling, B 2 O 3 The particles are fixed on the surface of the foam ceramic pores.
[0062] Performance test, the solid B 2 O 3 The foam ceramic particles were placed in 150ml, 50mg / L methylene blue solution, and the photocatalytic performance was tested under ultraviolet light and repeated for multiple cycles. The results showed that after 450min, the degradation rate reached more than 80.24%, and after 10 regeneration cycles, the degradation rate could still reach more than 79.68%.
[0063] Example 4
[0064] Weigh 1g of nano-BVO 4Powder, 2g polyvinyl butyral, 0.3g ethylene acrylic acid, 1g butyl benzyl phthalate, 20g methanol and 5g ethyl acetate were poured into a beaker and stirred at 600r / min for 24h using a magnetic stirrer to form a viscous slurry of BVO 4 Slurry.
[0065] Immerse all the cleaned and dried foam ceramic blocks in the slurry and keep them for 30 seconds. After slowly extracting them, place them in a cool place to dry. After the slurry on the surface of the foam ceramic solidifies, perform the second immersion. The immersion method is the same as the first immersion method. The foam ceramics after immersion are placed in a cool place to dry. After they are completely dry, they are calcined at low temperature in a muffle furnace. The calcination temperature is 300℃ and the temperature is kept for 4 hours. After cooling, BVO 4 The particles are fixed on the surface of the foam ceramic pores.
[0066] Performance test, the solid B 2 O 3 The foam ceramic particles were placed in 150ml, 50mg / L methylene blue solution, and the photocatalytic performance was tested under ultraviolet light and repeated for many times. The results showed that after 450min, the degradation rate reached more than 81.68%, and after 10 cycles, the degradation rate could still reach more than 80.47%.
[0067] Obviously, the above-mentioned embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the embodiments of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made on the basis of the above description. It is impossible to list all the embodiments here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.
Claims
1. A method for immobilizing a photocatalyst on a foam ceramic, characterized in that: The following steps are involved: Step 1: Mix the nano-photocatalyst with an organic binder, a dispersant, a thickener and an organic solvent in proportion and mix them evenly to obtain a viscous photocatalyst slurry; Step 2: Clean the foam ceramic to ensure that there are no impurities inside the foam ceramic, and cut it into any required size; Step 3: Immerse the cleaned foam ceramics in the viscous photocatalyst slurry, take them out and dry them; Step 4: After the foam ceramic loaded with the photocatalyst slurry is completely dried, it is calcined at a low temperature, and the nano-photocatalyst can be fixed on the pore surface of the foam ceramic.
2. The method for immobilizing photocatalyst on foam ceramics according to claim 1, characterized in that: In step 1, the organic binder includes: acrylates, alkyd resins, polyurethanes or epoxy resins; the dispersant includes: fatty acids, aliphatic amides, esters or low molecular waxes; the thickener includes: polysaccharide or polypeptide thickener; the organic solvent includes: alcohols, ketones, aromatic hydrocarbons, aliphatic hydrocarbons, aliphatic hydrocarbons, halogenated hydrocarbons, ethers or lipids.
3. The method for immobilizing photocatalyst on foam ceramic according to claim 1 or 2, characterized in that: In the step 1, the photocatalyst is an inorganic semiconductor material photocatalyst; the ratio of nano photocatalyst particles to organic binder, dispersant, thickener and organic solvent refers to that the nano photocatalyst content is greater than or equal to 1%wt of the total mass, the organic binder is 1% to 30%wt of the total mass, the dispersant is 0.1 to 10%wt of the total mass, the thickener is 0.1% to 10%wt of the total mass, and the rest are organic solvents, and the organic solvent is greater than or equal to one type of solvent used alone or in combination.
4. The method for immobilizing photocatalyst on foam ceramics according to claim 1, characterized in that: In the step 1, the mixing method includes ball milling and stirring; the amount of balls added to the ball mill is not less than 20% of the volume of the ball mill, the diameter of the grinding balls is 5 mm to 20 mm, the ball milling speed is not less than 100 rpm, and the ball milling time is not less than 5 min; the stirring is magnetic stirring or mechanical stirring, the stirring speed is not less than 100 rpm, and the mixing time is not less than 10 min.
5. The method for immobilizing photocatalyst on foam ceramics according to claim 1, characterized in that: In the step 2, the foam ceramic refers to foam ceramic with an average pore size of 40 ppi or more; and the cleaning is carried out by ultrasonic cleaning or water washing.
6. The method for immobilizing photocatalyst on foam ceramics according to claim 1, characterized in that: In the step three, the immersion refers to completely immersing the foam ceramic in the slurry, the immersion time is not less than 2 seconds, and the number of immersions is not less than 1 time; and the drying refers to natural drying in a cool and ventilated place.
7. The method for immobilizing photocatalyst on foam ceramics according to claim 1, characterized in that: In the step 4, complete drying means that there is no sticky slurry on the surface of the foam ceramic; the temperature of low-temperature calcination is 200°C-700°C; the temperature is kept for more than 10 minutes, and after cooling, the nano-photocatalyst can be fixed on the surface of the foam ceramic pores; the heating rate is 1-20°C / min, and the low-temperature calcination uses an atmosphere furnace, a vacuum furnace or a non-atmosphere furnace.
8. The method for immobilizing photocatalyst on foam ceramics according to claim 1, characterized in that: In the step 4, a double-layer atmosphere furnace is used for low-temperature calcination, comprising an outer shell (1), an inner side of the outer shell (1) is provided with an insulating inner seat (2), a heating resistance wire is provided on the inner side of the control outer shell (1) and at the lower end of the insulating inner seat (2), an outer furnace body (5) is fixed on the inner side of the insulating inner seat (2), a first feeding cavity (7) is provided inside the outer furnace body (5), an outer furnace door (3) is provided on the outer side of the outer shell (1) and at the outer side of the first feeding cavity (7), the outer furnace door (3) is fitted with the insulating inner seat (2), an inner furnace body (6) is fixed on the inner side of the outer furnace body (5), a second feeding cavity (16) is provided inside the inner furnace body (6), and a first feeding cavity (16) is provided inside the outer furnace body (5) and at the inner side of the first feeding cavity (7). A support shaft (14) is rotatably connected between the feeding cavity (7) and the second feeding cavity (16), an inner furnace door (15) is fixed on the outer side of the support shaft (14), and the inner furnace door (15) is fitted with the inner furnace body (6); a cooling pipe (10) is fixed on the inner side of the upper end of the outer shell (1), and the lower end of the cooling pipe (10) is respectively located inside the heat-insulating inner seat (2), the outer furnace body (5), and the inner furnace body (6) and is fixed to the heat-insulating inner seat (2), the outer furnace body (5), and the inner furnace body (6); an air inlet pipe (8) and an air outlet pipe (9) are respectively fixed on the top end of the outer shell (1), and the lower ends of the air inlet pipe (8) and the air outlet pipe (9) both penetrate the outer furnace body (5) and extend to the inner side of the outer furnace body (5).
9. The method for immobilizing photocatalyst on foam ceramics according to claim 8, characterized in that: An electromagnetic valve (4) is arranged between the outer side of the heat-insulating inner seat (2) and the outer furnace door (3); a reduction motor (11) is fixed on the inner side of the outer shell (1); a coupling (12) is fixed on the output end of the reduction motor (11); the coupling (12) is made of heat-insulating material; one end of the coupling (12) away from the reduction motor (11) passes through the outer furnace body (5) and is fixed to the support shaft (14); an insulation jacket (13) is fixed on the outer side of the inner part of the outer furnace body (5) and between the coupling (12) and the support shaft (14); the outer sides of the coupling (12) and the support shaft (14) are both in contact with the inner side of the insulation jacket (13); the coupling (12), the insulation jacket (13) and the support shaft (14) are coaxially arranged.
10. The method for immobilizing photocatalyst on foam ceramics according to claim 8, characterized in that: A plurality of heat conducting plates (17) are evenly fixed to the top of the inner side of the inner furnace body (6), and the upper ends of the plurality of heat conducting plates (17) are all in contact with the cooling pipe (10). The cooling pipe (10) is located outside the outer shell (1), and the outer periphery is coated with a heat-insulating material.